Hermeneutik Ekoteologi Samagaha Berdasarkan Kalender Hijriah Sebagai Pertobatan Ekologi - Ridha Herdiani; Muchtar Solihin; Munir (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2025)
Amid global crises threatening Indonesian agrarian sustainability, this study asks How can Sundanese eclipse interpretations as ayat kauniyah be revitalized via ecotheology for sustainable Islam Nusantara identity? Ecotheology sees eclipses as divine signs urging khalifah fil ardhi reflection, per Nasr: “In the eye of a spiritual person, every organism of nature reflects the divine reality…”1 Background Sundanese reliance on natural cycles in 19th-century naskah patakonan, endangered by deforestation and climate change. Bridging global works like Siregar et al.,2 it adds local reinterpretation of Batara Kala myth eclipse devourer as shirk-free ecological warning, akin to Murniati.3Qualitative method integrates Gadamerian hermeneutics fusion of horizons4 and semiotics pre-understanding agrarian context, explanation shafar symbols, application (QS. Fushilat: 37, khusuf hadiths). Primary naskah patakonan data triangulated with ecotheology literature. Findings unpack 12 interpretations, transforming 75% agrarian omens Safar drought, Jumadil Akhir floods into repentance narratives. Key results khusuf ritual, reforestation, ecological sermons for Sundanese madrasahs, nature-inclusive local Islam model, supporting Kemenag's 2025–2029 green curriculum.